Influence of the addition of Half-Heusler nanoparticles on the thermoelectrical properties of an N-type magnesium–silicon–tin alloy. (15th July 2015) - Bernard-Granger, Guillaume; Vracar, Radivoje; Navone, Christelle; Leforestier, Jean; Boidot, Mathieu; Carrete, Jesús; Deniau, Benoit; Simon, Julia
Abstract : The addition of 1.7 vol.% of MgCuSn Half-Heusler nanoparticles and the optimization of the size/concentration of nanometer-sized inclusions/nodules homogeneously dispersed in the sintered microstructure are thought to reduce strongly the lattice-thermal conductivity of an N-type polycrystalline Mg2 Si x Sn1 − x thermoelectrical material. Accordingly the dimensionless figure of merit (ZT) approaches 1.3–1.4 at 510 °C.